DYNAMICS PERFORMANCE OPTIMIZATION OF DELTA PARALLEL MECHANISM - ZHANG FengTao; SHI GeMeng; HAN YaFeng (Jixie qiangdu)
The dynamics modeling of Delta parallel mechanism is established by using of Kane’s equation,and dynamics equation is expressed by simple generalized active force and inertial force. The maximum of joint driving torque in the whole program space is regarded as the global performance indices to quantify the dynamics performance of mechanism,meanwhile requirement of program space is treated as constraint of structure parameter. Dynamics performance of the mechanism is optimal based on the performance index,and both demand of programming space and dynamics performance are considered. Be the performance index as the multiple functions of structural parameters,quantitative the direction and magnitude of performance index variation with the aid of sensitivity,in order to avoid the blindness of the process. Performance index is not sensitive to parameter perturbation,good for the body to maintain its excellent raw performance for a long time.